Religious fasting and its impacts on individual, public, and planetary health: Fasting as a “religious health asset” for a healthier, more equitable, and sustainable society - Trabelsi, Khaled; Ammar, Achraf; Boujelbane, Mohamed Ali; Puce, Luca; Garbarino, Sergio; Scoditti, Egeria; Boukhris, Omar; Khanfir, Saber; Clark, Cain C. T.; Glenn, Jordan M.; Alhaj, Omar A.; Jahrami, Haitham; et al. (Frontiers in Nutrition, 2022)
Religious fasting is practiced by people of all faiths, including Christianity, Islam, Buddhism, Jainism, as well as Hinduism, Judaism, and Taoism. Individual/clinical, public, global, and planetary health has traditionally been studied as separate entities. Nevertheless, religious fasting, in conjunction with other religious health assets, can provide several opportunities, ranging from the individual to the population, environmental, and planetary levels, by facilitating and supporting societal transformations and changes, such as the adoption of healthier, more equitable, and sustainable lifestyles, therein preserving the Earth's systems and addressing major interconnected, cascading, and compound challenges. In this review, we will summarize the most recent evidence on the effects of religious fasting, particularly Orthodox and Ramadan Islamic fasting, on human and public health. Further, we will explore the potential effects of religious fasting on tackling current environmental issues, with a special focus on nutrition/food restriction and planetary health. Finally, specific recommendations, particularly around dietary intake during the fasting rituals, will be provided to ensure a sustainable healthy planet.